(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Monoclonal gammopathy are haematologic disorder characterized by abnormal production of one or more immunoglobulin clone. Accurate detection and quantitation of monoclonal immunoglobulins is important for diagnosis and management of monoclonal gammopathies.There are very few studies related to monoclonal gammopathy in Bangladesh. This study wasaimed to observe the clinical profile and immunoglobulin pattern of monoclonal gammopathy cases in a tertiary care referral center. Objective: This study wasaimed to observe the clinical profile and immunoglobulin pattern of monoclonal gammopathy cases in a tertiary care referral center. Methodology: This cross sectional study was conducted in the Department of Haematology, Armed Forces Institute of Pathology (AFIP), Dhaka Cantonment, Dhaka. Study Period was July 2014 to Dec 2014. Patients with the age between 40 to 70 yearsof both sexes who were diagnosed as cases of monoclonal gammopathies was selected as study population. All patients were interviewed by using standard questionnaire and general medical condition of the patients was evaluated through history taking, clinical examination and laboratory investigations. Bone marrow microscopic examination, serum protein electrophoresis, immunofixationelectrophoresis (IFE), skeletal survey and relevant biochemical tests including serum creatinine, calcium, albumin and urinary BJP were performed. Protein electrophoresis of the samples was performed by automated capillary electrophoresis machine. Results: A total of 30 cases were recruited for this study. Out of 30 monoclonal gammopathy cases, majority of cases 17(56.7%) were between 60 to 70 years age group. Mean age was 57.13(±9.66) years. Male were predominant 19(63.0%) and Male female ratio was 1.72:1. Among the patients, low backache and pallor was common in majority (80%) of the cases, while fatigue and fever were present in 73.3% and 70.0% cases respectively. Among the patients, 7(23.3%) were hypertensive, 6(20.0%) were diabetic, 3(10.0%) patients were suffering from CKD with hypertension, 3(10.0%) had bronchial asthma, 1(3.3%) was with hypertension and Diabetes Mellitus. Depending on different laboratory findings, among all the 30 cases, 21(70%) cases were diagnosed as multiple myeloma, 5(16.6%) cases were MGUS and 2(6.7%) cases were Smouldering multiple myeloma and kappa light chain multiple myeloma each. Among the multiple myeloma cases, 11(36.6%) cases had IgG Kappa monoclonal gammopathy and 6(20.0%) cases had IgG Lambda monoclonal gammopathy. Conclusion: Monoclonal gammopathy occurs predominantly in male population at around sixth decade and mostly are presented with fatigue and bone pain. Majority of the patients suffered from multiple myeloma. Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 19-23